PEMBELAJARAN FISIKA BERBASIS PRAKTIKUM PHYPHOX MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI TERBIMBING - Stoni Suoth; Patricia Silangen; Jeane Rende (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2023)
This study aims to determine the ability of students to understand the concept of rolling motion through Phyphox practicum-based learning using the guided inquiry model. This study uses a guided inquiry model which consists of three stages, namely initial knowledge tests, practicum-based learning activities and final knowledge tests. This study uses a percentage analytical descriptive technique, namely by calculating the percentage value of the initial ability test results, the final ability test using the N-Gain and practicum performance assessment scores (roll's experiment) in the learning process. The research is located in the Department of Physics FMIPA-K UNIMA. A sample of active semester 5 students majoring in physics for the 2022/2023 academic year with 15 research subjects. The results of data processing and analysis obtained an average initial test score of 14.33 and an average final test value of 89.2 and performing statistical tests with the N-Gain test obtained an average result of 0.87 so that there was an increase in student physics learning outcomes after applying the treatment and the results of the practicum performance assessment (Roll's Experiment) in the learning process with an average task achievement of 88.75% so that there is an understanding of physics concepts in students.